2008
DOI: 10.1510/icvts.2008.191619
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgery in the management of pleuropulmonary tuberculosis - seven years' experience at a single institution

Abstract: Pleuropulmonary tuberculosis (TB) is a relatively frequent condition (the incidence of (TB) was 176/100,000 in our county in 2004) and some of these patients with TB are undergoing surgical interventions. The authors share their experience in surgical treatment of pleuropulmonary tuberculosis, based on minimal invasive techniques such as VATS and filling the residual cavities with muscle or skin-muscle grafts. The authors are retrospectively revising 144 patients between 1 January 2001 and 31 December 2007 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…However, it remains unclear whether VATS is more useful in such advanced disease stage, since more studies with large patient pool are required to support the data obtained in isolated clinical observations. 19,20) It was suggested that VATS for tuberculous empyema is effective only for stage II disease, and open thoracotomy and decortication are indicated for stage III empyema. 19) The conversion and reoperation rates were low for early stages, suggesting the thoracoscopic approach as effective and reasonable first option for most patients with complex pleural effusions and empyema.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether VATS is more useful in such advanced disease stage, since more studies with large patient pool are required to support the data obtained in isolated clinical observations. 19,20) It was suggested that VATS for tuberculous empyema is effective only for stage II disease, and open thoracotomy and decortication are indicated for stage III empyema. 19) The conversion and reoperation rates were low for early stages, suggesting the thoracoscopic approach as effective and reasonable first option for most patients with complex pleural effusions and empyema.…”
Section: Discussionmentioning
confidence: 99%
“…If pleural empyema occurs with radiologic TB signs, conservative treatment with prolonged chest tube aspiration is strongly recommended. Surgical therapy (open approach) is suggested only for cases with major residual pleural thickenings (89).…”
Section: Treatment Of Tuberculous Pleural Empyemamentioning
confidence: 99%
“…However, considering the increasing incidence of TB [4,9] and other intrathoracic infections, this kind of surgery may be required more often in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant advances in the treatment of thoracic infections, they remain a problem for the modern thoracic surgeon [1][2][3][4]. Patients not amenable to lung resection or decortication remain a major challenge since they often require prolonged hospitalisation, multiple procedures and mutilant surgery [5].…”
Section: Introductionmentioning
confidence: 99%